Study the characteristics of TDA7000 ic on multiband receiver / Roslan Shaul Hamid - Hamid, Roslan Shaul (2013)
A multiband receiver is a one of the group of frequencies system which receives only. Basically, it is an amplified type of "crystal radio" designed to receive AM transmissions. The "receiver" design uses no oscillators or other RF circuitry capable of interfering with aircraft communications. This study discusses the characteristics of the TDA7000 ic on multiband receiver by observe the effect of resistor and inductor to the voltage range as replacement for the frequency range. This study was carried out by build a multiband receiver circuit. Then, measurement of the input voltage and output voltage is conducted. From the data obtained, calculation for voltage gain is made. This study found that the voltage range for the receiver will presented in the graph. Lastly, the multiband receiver is type of radio wave that is important to carry information from one place to another by using air as a medium.